2015
DOI: 10.1519/jpt.0000000000000029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Dual-Task Net-Step Exercise on Cognitive and Gait Function in Older Adults

Abstract: This study shows that dual-task NSE is capable of improving cognitive and gait performance in healthy older adults. Our results indicate that NSE offers an option for a large segment of the older population who need an easier way to maintain their cognitive health and gait function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 27 publications
2
43
0
Order By: Relevance
“…The NSE features characteristics of a dual task exercise with additional cognitive tasks (e.g., learning the steps, paying attention to the net while stepping over it) and walking at a slow pace, unlike aerobic exercise. In the previous study, low-frequency intervention of NSE (once a week) improved cognitive and gait functions in people 73 years or older ( Kitazawa et al, 2015 ). Moreover, NSE requires mutually interactive group participation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The NSE features characteristics of a dual task exercise with additional cognitive tasks (e.g., learning the steps, paying attention to the net while stepping over it) and walking at a slow pace, unlike aerobic exercise. In the previous study, low-frequency intervention of NSE (once a week) improved cognitive and gait functions in people 73 years or older ( Kitazawa et al, 2015 ). Moreover, NSE requires mutually interactive group participation.…”
Section: Discussionmentioning
confidence: 94%
“…NSE uses a net and features slow and low-impact physical movement and cognitive activity. Kitazawa et al (2015) reported that an NSE intervention conducted just once a week improved cognitive and gait function. This program is also intended to serve as an opportunity for social participation among older people by promoting group exercise.…”
Section: Introductionmentioning
confidence: 99%
“…However, all these systems require their own specific sensors and have limitations in mobility, and it is rare with a smart application with wearable sensors. In addition, providing feedback if the users memorized the order of four notes correctly would be helpful to improve motivation and short-term memory function (Kitazawa, et al, 2015;Teixeira, et al, 2013). Even though a 4-note task only was tested in this test, longer sequence (up to 8-note task) will be more challenging and would be useful in the longterm training study with a special population who want to improve their physical and cognitive function.…”
Section: Functionalitymentioning
confidence: 99%
“…Short-term memory is a type of memory used to retain information for a short time (15-30 seconds) (Atkinson & Shiffrin, 1971). Previous studies revealed that a square stepping exercise, where the users were asked to memorize the number of blocks and step on each block in order, could improve cognitive functions (Kitazawa, et al, 2015;Teixeira, et al, 2013). To accomplish the abovementioned goals, it is necessary to have a userfriendly and well-functioning application.…”
Section: Introductionmentioning
confidence: 99%
“…DT's performance is related to most of the everyday life activities and the inability of patients to perform e cient tasks may have different consequences. Recently, several studies have been conducted on healthy elderly people [12][13][14][15] or in people with mental illnesses (e.g., Parkinson's disease) [16] using DT exercises, whose results showed improvement of balance and walking. indirectly, the bene ts of walking and learning separately indicate that performance in these tasks can be improved in patients with targeted interventions.…”
Section: Introductionmentioning
confidence: 99%